0058 Circadian Variation Of The Efficacy Of Intravenous Recombinant Tissue Plasminogen Activator In Patients With Acute Ischemic Stroke. (27th April 2018) - Kim, J; Lee, S
Abstract: Introduction: Among several physiologic factors to influence the occurrence of ischemic stroke, the serum concentration of plasminogen activator inhibitor-1 was shown to have clear circadian variation, which could influence platelet aggregation, blood viscosity, and endogenous/exogenous fibrinolytic activity. The aim of our study is to investigate whether the efficacy of intravenous recombinant tissue plasaminogen activator (r-tPA) could have circadian variation in patients with acute ischemic stroke and in the stroke subtypes according to etiologic mechanisms. Methods: Retrospectively, 1, 923 patients treated with IV r-tPA for acute ischemic stroke were identified from the Clinical Research Center for Stroke (CRCS) 5th division registry database in Korea. The patients were categorized by stroke onset time by every 4 hours (23-3h, 3-7h, 7-11h, 11-15h, 15-19h, and 19-23h). Stroke onset time was defined by last normal time. Demographic information and National Institute of Health stroke scales (NIHSS) were analyzed. For IV t-PA efficacy analysis, NIHSS at the emergency room (iNIHSS), NIHSS at 24 hours after IV r-tPA administration (day#1NIHSS), and a change of follow-up NIHSS (subtraction of day#1NIHSS from iNIHSS: cNIHSS) were used. Three stroke subgroups according to TOAST classification (large artery atherosclerosis, LAA; small vessel occlusion, SVO; cardio-embolism, CE) were separately reviewed. Results: The whole group analysis showed no statistically significant difference of NIHSS improvement according to the time of day of stroke onset although 23-3h group had the highest cNIHSS and followed by 3-7h group. LAA, CE group showed the same pattern as the whole group. cNIHSS of the 3-7h group was higher than that of 23-3h and other time of the day in patients with SVO group without statistical significance. Conclusion: Our study did not show a definite circadian variation of the efficacy of iv t-PA measured by NIHSS change at 24h after administration. Further subgroup analysis depending on the severity of initial neurologic dysfunction and a long-term outcome will be needed. Support (If Any): N/A.